PENGARUH PERTUMBUHAN PENJUALAN, PROFITABILITAS, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK DI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2021-2024 - Sri Ayu Hartini Handayani; Andar Febyansyah (Jurnal Riset Terapan Akuntansi, 2026)
The study aims to investigate the relationship between tax avoidance and ETR proxies such as sales growth (SG), profitability (ROA), firm size (TA), and leverage (DER) in manufacturing companies in various industrial sectors listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. Utilizing a purposive sampling method that meets the criteria, this study uses information taken from companies' annual financial reports. The study spanned four years, with 80 data sets from 20 manufacturing companies from various industries. Descriptive statistical analysis, classical assumption tests, hypothesis tests, and multiple linear regression tests were used with secondary data types in this study. In addition, SPSS data processing was also used. This study shows that overall, sales growth, profitability, firm size, and leverage have a significant influence on tax avoidance. Sales growth and leverage have a positive impact on tax avoidance. Meanwhile, profitability has a negative relationship with tax avoidance. Firm size has no influence on tax avoidance. Keywords: Sales Growth, Profitability, Company Size, Leverage, Tax Avoidance.